1970
DOI: 10.1002/art.1780130622
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary amyloidosis

Abstract: A review of hereditary amyloidoses is provided by papers from a 1969 international symposium on primary amyloidosis. These discussions allow comparison of the amyloid neuropathy with onset in the lower extremities (POrtUgueseJapanese families), the neuropathy with onset in the upper extremities (Indiana-Maryland families), the neuropathy and nephropathy of the Iowa family, and the amyloidosis of familial Mediterranean fever. The importance of studies of genetic entities in understanding the pathogenesis of amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1
1

Year Published

1981
1981
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 37 publications
1
31
1
1
Order By: Relevance
“…The finding that the relatively rare variants of two genetic markers in Japan, Gc*IA2 and PGMI*7, are distributed over the three genealogically independent families suggests that the families (Sa, U and Tu) may have a common ancester. Phenotypes attributable to Caucasians, for example K+ in the Kell blood group, were not found in the present study and hence no evidence was found for the hypothesis that the FAP gene in Arao was derived from the Portuguese (Andrade et al, 1970). Whether a few rather unusual findings in the ABO blood groups, the Kidd groups, the Hp and the Pi systems, reflect only the characteristics of FAP in the Arao district or that of FAP itself remains to be solved.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The finding that the relatively rare variants of two genetic markers in Japan, Gc*IA2 and PGMI*7, are distributed over the three genealogically independent families suggests that the families (Sa, U and Tu) may have a common ancester. Phenotypes attributable to Caucasians, for example K+ in the Kell blood group, were not found in the present study and hence no evidence was found for the hypothesis that the FAP gene in Arao was derived from the Portuguese (Andrade et al, 1970). Whether a few rather unusual findings in the ABO blood groups, the Kidd groups, the Hp and the Pi systems, reflect only the characteristics of FAP in the Arao district or that of FAP itself remains to be solved.…”
Section: Discussioncontrasting
confidence: 77%
“…The disease has a curious geographic distribution: there are large foci in Portugal (Andrade et al, 1969), Sweden (Andersson, 1976), and Japan (Araki et al, 1968;Kito et al, 1973), but the disease is uncommon elsewhere. Whether FAP in Japan has a Portuguese ancestry or not is an interesting enigma (Andrade et al, 1970). In a previous paper (Sakoda et al, 1983), we reported genealogical studies of FAP in the Arao district of Kumamoto prefecture.…”
Section: Introductionmentioning
confidence: 96%
“…phosphogluc0mutase 7 and group specific component J (Sakoda et al, 1984), we can conclude that five of the nine families have a common ancestor. Whether or not 'the FAP gene in the Arao focuS is derived from the Protuguese reamins an interesting enigma (Andrade et al, 1970): Second, it lends credence to the view that the prealbumin variant is essentially concerned with the pathogenic mechanism of this gerteticatly determined neuropathic disease. Although Tawara et aL: (1983) .~oL 29,, No;',:,3,, 1984 reserved an alternative possibility-that this prealbumin variant is a polymorphism of prealbumin, the findings of this study make it unlikely.…”
Section: Discussionmentioning
confidence: 96%
“…Extensive genetic studies have failed to reveal connection with any of the several kindreds with amyloidosis in the United States or with Portuguese kindreds (8).…”
Section: Discussionmentioning
confidence: 99%
“…Classical secondary amyloidosis associated with chronic inflammatory diseases has deposits that are composed of amyloid A (AA),' a degradation product of an acute phase reactant, serum AA (SAA) (6,7). A third commonly recognized type of systemic amyloidosis is seen with the heredofamilial syndromes (8).…”
Section: Introductionmentioning
confidence: 99%